#### Answer

$g(x)=(x-2)^{2}=x^{2}-4x+4$

#### Work Step by Step

We obtain $g(x)$ by shifting $f(x)=x^2$ two units to the right, i.e. $y=f(x-2)$:
$g(x)=(x-2)^{2}=x^{2}-4x+4$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$g(x)=(x-2)^{2}=x^{2}-4x+4$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.